Process modelling of sugar mill biomass to energy conversion processes and energy integration of pyrolysis - Nsaful, Frank (Stellenbosch : Stellenbosch University, 2012)
ENGLISH ABSTRACT: The sugar industry over the years has been producing sugarcane bagasse as part of the sugar milling process. Currently this sugar mill biomass is incinerated inefficiently as a means of their disposal to produce steam and electricity, which in most cases are only just enough to supply the energy required to run the mills, thereby leaving very little or no extra energy for sale to bring in extra income in addition to sales revenue from sugar. However, the recent instability and uncertainties in the price of sugar and the global call for a green and sustainable environment have necessitated the search for ways of making effective use of this biomass to supply sugar mill energy demands, while producing extra energy in the form of electricity and other energy products for sale and at the same time contributing towards environmental sustainability. The main objective of this work was to develop process models for the processing of sugar mill biomass into energy and energy products. Based on this, biomass to energy conversion process (BMECP) models have been developed for various process configurations of two thermochemical processes; Combustion and Fast Pyrolysis using the Aspen Plus® simulation software. The aim of process modelling was to utilizing sugar cane bagasse as an input energy source to supply the energy requirements of two sugar mill configurations (efficient and less efficient mills), while generating extra electricity and high valued energy products for sale. Four BMECP configurations; 30bar BPST, 40bar CEST, 63bar CEST and 82bar CEST systems were modelled for the combustion thermochemical process. For the fast pyrolysis thermochemical process, two process configurations: Pure Fast Pyrolysis BMECP and Partial Fast Pyrolysis BMECP were modelled. The former BMECP utilizes all available bagasse through fast pyrolysis to produce bio-oil and biochar alongside generating electricity as well as energy to run the sugar mill operations. In the latter BMECP model, only surplus bagasse after separation of the quantity needed to supply the sugar mill energy requirement and electricity production is used to produce bio-oil and biochar. The technical performance of the BMECP models have been analysed and compared based on steam and electricity production rates, process efficiencies and environmental impacts (based on CO2 savings). The effects of boiler operating pressure and bagasse moisture content on the performance of the combustion based BMECP models have also been investigated. Finally, detailed economic models have been developed using the Aspen Process Economic Analyzer (Icarus®) to assess the economic viability of the BMECP models and sensitivity analysis performed to study the response of the BMECP models to variations in economic parameters. Technical performance analysis shows the combustion based BMECP models perform better than the Pure Fast Pyrolysis and Partial Fast Pyrolysis BMECP models with regards to steam and electricity production, thereby giving them higher electrical efficiencies. The electricity generation rate has been shown to increase with increasing boiler operating pressure and decreasing bagasse moisture content while steam production rate has been shown to increase with decreasing bagasse moisture content and decreasing boiler operating pressure. Despite the lower electrical efficiencies of the fast pyrolysis based BMECP models, the analysis shows that their overall process efficiencies compare very well with those of the combustion based BMECP models due to the production of high energy value pyrolysis products. Based on common operating pressure and 50% bagasse moisture content, the Pure Fast Pyrolysis and the Partial Fast Pyrolysis models have proved to be more environmental friendly with hourly CO2 savings of 40.44 and 41.30 tons for the Partial Fast Pyrolysis BMECP and the Pure Fast Pyrolysis BMECP respectively based on a 300 ton of sugarcane/h (81 ton bagasse/h) plant size. From an economic point of view, biomass combustion based on the 63bar CEST BMECP model has proved to be the most economically viable option under current economic conditions. First order total capital investment estimate for this BMECP is about $116 million, producing NPV of $390 million at the end of a 20 year plant life and IRR of 34.51%. The Pure Fast Pyrolysis BMECP model is the least economic viable option. Sensitivity analysis shows this BMECP model is the most sensitive to changes in bagasse and electricity prices; recording -191.61/+446.86% change in NPV for a ±30% change in bagasse price and -91.5/+338.60% for a ±30% change in electricity price.